Prospek Pengembangan Sistem Pertanian Terpadu Tanaman Padi Sawah dengan Ternak Sapi di Kecamatan Wonosari Kabupaten Boalemo - Wibowo, Hadi Setyo; Indriani, Ria; Adam, Echan (Universitas Galuh, 2024)
This research aims: 1) To determine the feasibility of integrated farming systems of paddy rice and beef cattle in Wonosari District, Boalemo Regency, 2) To identify the internal and external factors in the development of integrated farming systems of paddy rice and beef cattle in Wonosari District, Boalemo Regency. This research was conducted from February 2023 to April 2023 with a sample of 39 respondents. The research method employed descriptive and quantitative methods. The data analysis utilized R/C Ratio analysis and SWOT analysis. The research results indicated that integrated farming systems of paddy rice with beef cattle were feasible based on the income received per farmer amounting to 17.624.861/year with an R/C Ratio of 1.50. Factors affecting the prospects of integrated farming systems include supportive environments, the use of agricultural technology, support from agricultural departments, easily marketable products, and farmers' high level of experience in farming development.